Formulation of Ready to Drink (RTD) Made from Roselle (Hibiscus Sabdariffa. L) Tea and Stevia (Stevia Rebaudiana) Leaf Safe for Diabetics - Saraswati AR; Mardiah; Taniwiryono D (Universitas Djuanda, 2020)
Diabetic is a degenerative disease that has become a public concern. Several studies have shown that roselle tea extracts can reduce blood glucose levels by improving the pancreatic glands, and Stevia rebaudiana leaf has zero calorie with a sweetness coming from diterpene glycosides (stevioside and rebaudioside-A) which are safely metabolized in body, so that it can be used as sweetener for diabetics. The purpose of this study was to determine the formula of roselle tea and stevia leaf that is safe for diabetics. Three formulas of ready to drink (RTD) were prepared using 2% (w/v) rosella tea with 0.1, 0.3, and 0.5% (w/v) stevia leaf, then the sensory qualities were analyzed including the red color, sweetness, bitterness, off flavor. The selected formula was RTD made from 2% (w/v) roselle tea and 0.3% (w/v) stevia leaf. The RTD had a little bright red color, pretty sweet, no bitter taste, quite off flavor, and total microbes < 2.5 EAPC (compromise with Indonesian Standard Regulation for fruit juice). Carbohydrate content (Anthrone method) of RTD roselle-stevia and roselle-sugar was 0.1507% and 1.3293%. Effect analysis of RTD roselle-stevia and roselle-sugar on blood glucose levels of healthy patients based on ISO 26642:2010 measured every 30 minutes for 90 minutes and using t-test showed that RTD roselle-stevia did not affect (p>0.05) the increase in blood glucose levels, whereas RTD roselle-sugar did (p<0.05). It can be concluded that RTD containing 2% (w/v) roselle tea and 0.3% (w/v) stevia leaf is safe for diabetics.